2019
DOI: 10.3390/su11215935
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Evaluation of Mechanical Properties of Slag Based Alkali-Activated Material

Abstract: Slag is one of the by-products of the energy industry, which is suitable for secondary industrial processing. Although slag has been successfully used in industrial production for several decades, its use does not achieve the level of its potential. Today, to achieve a sustainable construction industry, alternative types of cement have been extensively investigated. Geopolymer is a kind of material which is obtained from the alkaline activator and it can be produced from the industrial wastes or by-products. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“… 55 57 Commonly used ratios fall within the range of 0.6 to 2 with the authors reporting various optimum values. 57 62 It was necessary to determine the minimum Ms that would help to achieve a workable solution. Figure 6 compares the behavior of alkaline solutions with Ms of 0.7, 0.9, and 1.1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 55 57 Commonly used ratios fall within the range of 0.6 to 2 with the authors reporting various optimum values. 57 62 It was necessary to determine the minimum Ms that would help to achieve a workable solution. Figure 6 compares the behavior of alkaline solutions with Ms of 0.7, 0.9, and 1.1.…”
Section: Resultsmentioning
confidence: 99%
“…The silicate modulus (Ms) of the sodium silicate solution controls the extent of gepolymerization and hence affects parameters like setting, viscosity, and strength. Commonly used ratios fall within the range of 0.6 to 2 with the authors reporting various optimum values. It was necessary to determine the minimum Ms that would help to achieve a workable solution. Figure compares the behavior of alkaline solutions with Ms of 0.7, 0.9, and 1.1.…”
Section: Resultsmentioning
confidence: 99%
“…From the results, it is observed that the ratio of Si/Al varies from 3.13 to 4.56, which represent medium silica zeolites (range from 3 to 10). The range of Si/Al from 3.13 to 3.9 produces higher compressive strengths (Sisol et al, 2019) Durability and microstructure study 4.3 X-ray diffraction analysis XRD analysis was performed to investigate the crystalline phases of the samples and the effect of different exposure conditions at 2ϴ angles ranging from 10 to 70°. Table 4 and XRD graphs show that the AASC structure exhibits major crystalline phases of SiO 2 with a maximum peak at 2ϴ = 26.34°to 26.592°for all exposure conditions.…”
Section: Resultsmentioning
confidence: 99%
“…From the results, it is observed that the ratio of Si/Al varies from 3.13 to 4.56, which represent medium silica zeolites (range from 3 to 10). The range of Si/Al from 3.13 to 3.9 produces higher compressive strengths (Sisol et al , 2019)…”
Section: Resultsmentioning
confidence: 99%
“…Trochez et al [18] In some studies, the ratio criteria for geopolymer compositions were utilized with Na 2 O instead of Al 2 O 3 . An investigation was conducted by Sisol et al [19] on the SiO 2 /Na 2 O ratio and the content of Na 2 O as an alkali activated precursor to develop hardened blast furnace slag-based geopolymers. The varying ratios of SiO 2 /Na 2 O at 0, 0.25, 0.5, 1.0, 1.2 and 1.4 were adopted in a series of investigations, to assess the mechanical strength of compositions.…”
Section: Industrial Waste Materials and Their Chemical Compounds/elementsmentioning
confidence: 99%